Managing Human Resource Quality: Insights From the Campus Retail Unit of UIN Sunan Gunung Djati - Dewi Kania (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Service quality in campus retail increasingly depends on human resource capability and operational discipline, making it essential to understand how these elements shape customer experience. This study aims to examine the role of human resource development, operational discipline, and interpersonal competence in enhancing service quality within campus retail units. The theoretical framework refers to Human Resource Development 4.0, High-Performance Work Systems, and Customer Experience Quality. This research employs a qualitative case study design through in-depth interviews, observations, and document analysis. Findings reveal that continuous training, consistent SOP implementation, and staff interpersonal competence significantly strengthen service stability and responsiveness. These results highlight the need for integrating human development and operational systems to achieve adaptive, customer-oriented service performance.